« Se situer » dans le nouveau système décisionnel au Sahara Occidental. Les élections régionales à Dakhla-Oued Eddahab - Victoria Veguilla del Moral (L’Année du Maghreb)
In the 2000s, the issue of decentralization re-emerged in Morocco following some events on the international agenda: the acceptance of the Baker II Plan by the Polisario Front (2002) and the presentation of the Advanced Autonomy Plan by Morocco (2007). Those have indeed updated the link between the files of « decentralization » and those of Western Sahara. This paper addresses the singularities of the implementation process of « decentralization » in this particular space, Western Sahara, taking as an angle of analysis the elections in Dakhla-Oued Eddahab, one of the three territorial and administrative regions planned by Morocco. More specifically, we propose to analyze struggle between the main local political actors in order to invest a regional institutional position capable of linking the Sahara policy with a conflict of sovereignty.